The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.1097/aog.0000000000005476
|View full text |Cite
|
Sign up to set email alerts
|

Prolongation of the Menstrual Cycle After Receipt of the Primary Series and Booster Doses of mRNA Coronavirus Disease 2019 (COVID-19) Vaccination

Satoshi Hosoya,
Aurelie Piedvache,
Akari Nakamura
et al.

Abstract: OBJECTIVE: To quantitatively evaluate the effect of a booster vaccination dose against coronavirus disease 2019 (COVID-19) on menstrual cycle in a large-scale retrospective cohort study using a menstrual cycle tracking smartphone application (app). METHODS: Prospectively or retrospectively recorded data, including the start and finish dates of menstrual cycles, were collected with the app. Detailed data on vaccinations, side effects, and participants' c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 33 publications
(52 reference statements)
0
3
1
Order By: Relevance
“…Here we provide the additional data requested by Hosoya et al detailing the change in lengths of follicular and luteal phases (Table 1) after coronavirus disease 2019 (COVID-19) vaccination, by timing of vaccination. We did not find similar changes in the follicular or luteal phase for people vaccinated in the follicular phase as published in Hosoya et al 1 The increase in follicular phase length that we observed 2 is smaller (approximately 1 day compared to 2–3 days in Hosoya et al), and we did not observe a decrease in luteal phase length. However, we did see a slightly shorter follicular phase for individuals vaccinated in the luteal phase, but these individuals received their vaccination after the completion of their follicular phase, so this finding is not due to vaccine exposure.…”
contrasting
confidence: 57%
See 1 more Smart Citation
“…Here we provide the additional data requested by Hosoya et al detailing the change in lengths of follicular and luteal phases (Table 1) after coronavirus disease 2019 (COVID-19) vaccination, by timing of vaccination. We did not find similar changes in the follicular or luteal phase for people vaccinated in the follicular phase as published in Hosoya et al 1 The increase in follicular phase length that we observed 2 is smaller (approximately 1 day compared to 2–3 days in Hosoya et al), and we did not observe a decrease in luteal phase length. However, we did see a slightly shorter follicular phase for individuals vaccinated in the luteal phase, but these individuals received their vaccination after the completion of their follicular phase, so this finding is not due to vaccine exposure.…”
contrasting
confidence: 57%
“…Likely this difference in findings between the two studies is due not only to our larger sample size but, more importantly, the data source. The data from the menstrual cycle tracking application used in Hosoya et al 1 do not include an ovulation date. Luteal phase was defined as the last 14 days of the cycle.…”
mentioning
confidence: 99%
“…The peak plasma concentration of betamethasone is reached by 12 hours, whereas betamethasone acetate acts as a reservoir for sustained action. 3 The time of maximum plasma concentration is the same for both, which is 3 hours, although the combination has a multiphasic concentration that lasts for up to 2 weeks or more. 4 In women in whom preterm labor is inevitable, the preferred drug of choice is one with quick onset of action, and prolonged steroid exposure is undesirable.…”
Section: In Replymentioning
confidence: 99%
“…We show results from data used in our study, “Prolongation of the Menstrual Cycle After Receipt of the Primary Series and Booster Doses of mRNA Coronavirus Disease 2019 (COVID-19) Vaccination,” 3 which limited cycles to those with ovulation date estimable from logged basal body temperature with the Sensiplan method. 4 We found that the prolongation of menstrual cycle length after vaccination during the follicular phase is a combination of a 2–3-day prolongation in the follicular phase and a 1–2-day shortening of luteal length (Table 1).…”
mentioning
confidence: 99%